Effect of loading configuration on strength values in a highly transformable zirconia-based composite. Issue 9 (September 2016) - Touaiher, Imane; Saâdaoui, Malika; Chevalier, Jérôme; Reveron, Helen
Abstract: Objectives: The aim of this work was to determine mechanical properties of a highly transformable 10Ce-TZP/Al2 O3 /La2 AlO3 composite, currently developed as a biomaterial for dental application, and to investigate the effect of loading configuration on its flexural strength. Methods: Fracture toughness is determined by the single-edge-V-notched beam (SEVNB) method. Strength measurements were conducted by four-point bending and biaxial bending tests (piston-on-three balls) according to ISO 6872, dedicated to ceramic materials in dentistry. Results: Strength obtained by either four-point or biaxial bending are very different, and take the values of 596 MPa and 1470 MPa respectively. It is demonstrated that the difference in measured strength cannot be attributed to the effect of volume on strength, generally predicted by the standard Weibull analysis, but to different transformation behaviors for the two bending configurations. More extensive transformation occurs in the biaxial configuration, with a lower autocatalytic transformation stress threshold, resulting to substantial compressive residual stresses. Significance: The significant influence of the loading configuration on the strength should be integrated when designing a component from a highly transformable ceramic.